Fabrication of Gelatin/PCL Electrospun Fiber Mat with Bone Powder and the Study of Its Biocompatibility - Rong, Dongming (J Funct Biomater, 2016)
Fabricating ideal scaffolds for bone tissue engineering is a great challenge to researchers. To better mimic the mineral component and the microstructure of natural bone, several kinds of materials were adopted in our study, namely gelatin, polycaprolactone (PCL), nanohydroxyapatite (nHA), and bone powder. Three types of scaffolds were fabricated using electrospinning; gelatin/PCL, gelatin/PCL/nHA, and gelatin/PCL/bone powder. Scaffolds were examined using scanning electron microscopy (SEM) and transmission electron microscopy (TEM) observations. Then, Adipose-derived Stem Cells (ADSCs) were seeded on these scaffolds to study cell morphology, cell viability, and proliferation. Through this study, we found that nHA and bone powder can be successfully united in gelatin/PCL fibers. When compared with gelatin/PCL and gelatin/PCL/nHA, the gelatin/PCL/bone powder scaffolds could provide a better environment to increase ADSCs’ growth, adhesion, and proliferation. Thus, we think that gelatin/PCL/bone powder has good biocompatibility, and, when compared with nHA, bone powder may be more effective in bone tissue engineering due to the bioactive factors contained in it.